Lua2NCL - Framework for Textual Authoring of NCL Applications using Lua - Moraes, Daniel de Sousa; Damasceno, André Luiz Brandao de; Busson, Antonio José G.; Neto, Carlos de Salles Soares (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia); 2016: Proceedings of the 22nd Brazilian Symposium on Multimedia and the Web, 2016)
Nested Context Language (NCL) is the standard declarative language used for the development of interactive digital TV applications in SBTVD (Brazilian Digital TV System) and ITU-T. Some previous researches show that NCL is more appropriate for content producers, whereas imperative languages are better for application developers. However, the size of NCL applications codes can reach levels that may affect even the legibility, which does not attract developers. The aim of this paper is to propose a framework, named Lua2NCL, to provide a set of textual features that enable the creation of applications for Digital TV without the same effort dispensed to the textual NCL authoring. These features offered by Lua2NCL have as their central focus the reduction in the verbosity of documents. This paper also presents two case studies performed with programmers showing that Lua2NCL can considerably reduce source codes, as well as, time spent in the authoring.